A discourse analysis of code-switching practices among Angolan migrants in Cape Town, South Africa - Da Costa, Dinis Fernando (University of the Western Cape, 2013)
Magister Artium - MA === In this thesis, I explore the code-switching practices of long-term Angolans migrants in Cape Town when they interact with those who have been here for a much shorter period. In my Honours research essay, I revealed a tendency among those who have lived in Cape Town for some time to code-switch from Portuguese to English even in the presence of more recent migrants from Angola, who have little or no mastery of English. This thesis thus considers the effects of space, discourses of power, language ideologies and attitudes on the patterns of inter- and intra-sentential code-switching by these long-term migrants in interaction with each other as well as with the more recent “Angolan arrivals” in Cape Town. Twenty Angolan migrants participated in this study. Of these, ten were long-term migrants to South Africa, while a further ten were relative newcomers. While the long-term migrants could claim to be bilingual in Portuguese and English, the newcomers were largely limited to a few English words in their repertoire. However, both groups could speak one or more of the indigenous languages of Angola, like Kimbundu, Umbundu, Kikongo and even Lingala (which is an indigenous language from Republic Democratic of Congo). Some of the long-term migrants had even acquired South African indigenous language such as isiXhosa and Afrikaans. The study made use of qualitative ethnographic methodologies to collect the data. These included recorded conversations, individual and focus group interviews, both general observation and participant observation. === South Africa